First determination of the spin-parity of Ξc(3055)+,0 Baryons - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Celani, Sara; Cocha Toapaxi, Carlos; De Cian, Michel; Dittmann, Lucas; Esen, Sevda; Glaser, Fabian; Günther, Paul André; Han, Xiaoxue; et al. (Physical review letters, 2025)
The Ξ0⁢(−)𝑏→Ξ𝑐⁢(3055)+(0)⁢(→𝐷+(0)⁢Λ)⁢𝜋− decay chains are observed, and the spin-parity of Ξ𝑐⁢(3055)+(0) baryons is determined for the first time. The measurement is performed using proton-proton collision data at a center-of-mass energy of √𝑠 =13 TeV, corresponding to an integrated luminosity of 5.4 fb−1, recorded by the LHCb experiment between 2016 and 2018. The spin-parity of the Ξ𝑐⁢(3055)+(0) baryons is determined to be 3/2+ with a significance of more than 6.5⁢𝜎 (3.5⁢𝜎) compared to all other tested hypotheses. The up-down asymmetries of the Ξ0⁢(−)𝑏→Ξ𝑐⁢(3055)+(0)⁢𝜋− transitions are measured to be −0.92±0.10±0.05 (−0.92±0.16±0.22), consistent with maximal parity violation, where the first uncertainty is statistical and the second is systematic. These results support the hypothesis that the Ξ𝑐⁢(3055)+(0) baryons correspond to the first 𝐷-wave 𝜆-mode excitation of the Ξ𝑐 flavor triplet.
The LHCb collaboration: R. Aaij, S. Bachmann, L. Carus, R. Caspary, S. Celani, C.E. Cocha Toapaxi, M. De Cian, L. Dittmann, S. Esen, F. Glaser, P.A. Günther, X. Han, S. Hausmann-Menzemer, P. Herrero Gascon, J. Hu, J. Kubat, C. Langenbruch, B. Leverington, J. Marks, M.P. Morgenthaler, P.R. Pais, S.R. Roy, M. Ruiz Diaz, M. Schmelling, G. Tuci, L.H. Uecker, D.J. Unverzagt, U. Uwer, C. Wang, L. Witola, M. Zavertyaev, Y. Zhao, A. Zhelezov und weitere 1104
Im Titel ist der Buchstabe "c" tiefgestellt und die Zeichen "+,0" hochgestellt
Gesehen am 20.10.2025